THE OBJECT OF STUDY, AIMS AND TASKS OF SOCIOLINGUISTICS - G’aniyeva Asila Otabek qizi (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This article explores the theoretical foundations, object of study, aims, and key tasks of sociolinguistics as a dynamic and interdisciplinary field within modern linguistics. The research focuses on the intricate relationship between language and society, emphasizing language variation, multilingual practices, discourse patterns, and the influence of social variables on linguistic behavior. Employing a combination of theoretical analysis, descriptive methodology, and discourse-oriented approaches, the study examines how sociolinguistic phenomena manifest in contemporary communicative environments. Particular attention is paid to the impact of globalization, digital communication, and language policy on linguistic evolution. The findings suggest that sociolinguistics plays a crucial role in understanding language as a socially embedded system and contributes significantly to education, intercultural communication, and social integration.